PROFILING ONLINE AND MANUAL TAX FILERS: RESULTS FROM AN EXPLORATORY STUDY IN PENANG, MALAYSIA - Ramayah, T.; Ramoo, Viveka; Ibrahim, Amlus (Labuan e-Journal of Muamalat and Society (LJMS), 2008)
The Malaysian Government has been promoting an Internet tax filing called the e-Filing which was introduced in 2006 as part of its E-government initiative. There has been some public outcry when the government announced that beginning 2007 they will not be sending the income tax forms and that all tax payers have to submit their taxes using this new method. After deliberation, the government has announced that both the system is acceptable and will be continued in the coming year. Although the Internet tax filing is a much more convenient and economical way of tax filing, not many tax payers have used them in their tax filing in the year 2006. Thus the purpose of this paper is to profile the users and non-users of the e-Filing method. This exploratory study elicited information using a structured questionnaire from 100 respondents from Penang. The results show not much difference in terms of the demographic profile of the online and manual tax filing except that Chinese respondents formed a bigger proportion of those who filed their taxes online compared to the other races. There were no significant differences in terms of sex, age, marital status, education level, occupation, income and some Internet usage statistics. One of the main issue was the 16-digit PIN number that was needed to be obtained directly from the income tax office was one of the barriers to many respondents. E-filers had less concern in terms of the risk as compared to the manual filers. Some recommendations are forwarded for the policy makers.